The Effectiveness of Gargling with Siwak Solution and Cinnamon Powder Towards Halitosis in Diabetes Mellitus - Mareta Suci Listari; Istianah; Baiq Nurainun Apriani Idris; Hapipah (Journal of Health Science Community, 2022)
Diabetes mellitus is a metabolic disorder characterized by hyperglycemia which can cause complications, one of which is halitosis caused by sympathetic and parasympathetic nervous disorders that cause saliva to become thicker or decrease salivary secretion. Using a mouthwash with a solution of siwak and cinnamon can help freshen breath and reduce halitosis. The purpose of the study was to determine the effectiveness of gargling with a solution of siwak and cinnamon powder on reducing the level of halitosis in people with diabetes mellitus in the working area of ​​Karang Pule public health center. This type of research is quasi-experimental with a Two Groups Pretest-Posttest Design approach. The number of samples was 18 people divided into two groups which were selected based on the matched subject ordinal pairing technique. The results of the Paired T-test analysis showed that gargling with a solution of siwak and cinnamon proved to be effective in reducing the level of halitosis with a p value of 0.000 (<0.05) and the results of the T-Independent analysis showed that there was no difference in the effectiveness of gargling with a solution of siwak and cinnamon powder in reducing the level of halitosis with a p value of 0.146. Based on research from siwak and cinnamon solution can be used as a gargle solution to reduce halitosis.